Chemotaxic biomimetic liquid metallic leukocytes - Ma, Yibing; Gao, Jianye; Guan, Tangzhen; Tao, Yiyue; Guo, Minghui; Liu, Jing (Matter, 2025)
The exceptional deformability and mobility of liquid-metal matter in aqueous environments confer significant potential in simulating various biomimetic behaviors. Here, inspired by biochemotaxis in nature, we fabricate a leukocyte-like liquid-metal entity that successfully simulates various leukocyte behaviors, such as self-phagocytosis, large-scale self-deformation, oscillatory self-propulsion, self-splitting and merging, and self-climbing opposing gravity. The intriguing mechanisms arise from the self-adapting surface tension of liquid metals, which is modulated by an environmentally oriented asymmetric chemical reaction that has discrepancies in tunable potential, metallic composition, and reactant ratios. Further findings demonstrate that this liquid entity can autonomously climb up to 5° slopes and traverse complex terrains. Moreover, it showcases robust deformability and impressive adaptability in obstacle navigation. It is anticipated that this functional entity will lay the foundation for future research, positioning liquid metals as a model for developing biomimetic living matter and advancing the construction of advanced nature-simulation systems. [Display omitted] •A biomimetic liquid metallic leukocyte is fabricated with liquid metals•Liquid-metal leukocyte shows diverse capabilities in emulating leukocytes’ motion•Chemotaxic mechanism is implemented to actualize autonomous behavior•The asymmetric factors that modulate the biomimetic leukocyte’s motion are disclosed Throughout scientific history, researchers have doggedly pursued the endowment of inanimate substances with the behavioral traits of living matter, steering toward the creation of synthetic life. However, contemporary studies hinging on external fields regularly come up short in concurrently attaining proficient movement and deformation. Herein, we conceived a chemotaxic liquid-metal system that mimics leukocyte behaviors, such as controllable self-propulsion, obstacle surmounting, climbing opposing gravity, and complex terrain traversal. The liquid-metal leukocyte system, with its behavioral versatility, holds immense promise for diverse applications, including flexible sensors and microfluidics. Moreover, by taking cells as a starting point, this system also paves the way for the further construction of liquid-metal-based biological tissues and even organs, heralding a new era of possibilities in the intersection of materials science and synthetic biology. A chemotactic biomimetic liquid-metal entity has been created, capable of simulating various autonomous behaviors resembling leukocytes in blood, including self-phagocytosis, large-scale self-deformation, oscillatory self-propulsion, self-splitting and merging, as well as self-climbing opposing gravity. This work not only pioneers a novel approach for achieving simultaneous self-propulsion and deformation of liquid robots without the need for external fields but also opens new avenues for developing innovative medical therapies that mimic leukocyte behavior.